Pengaruh Promosi Terhadap Perilaku Konsumen dalam Keputusan Pembelian di E-Commerce - Natasya Kinski; Raina Linda Sari; Dede Ruslan (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study is to see how the influence of promotions on consumer behavior in making decisions when buying goods in E-Commerce. This study used a quantitative method through data taken from the results of a questionnaire of 42 respondents in Medan. Then it was analyzed and processed using Excel and SPSS 22. This research was also carried out using qualitative methods by looking at the respondent's point of view. This study found that promotion had a negative and insignificant effect on consumer behavior in e-commerce. This is because consumers know to find out and do research on the specifications of goods and services before buying goods in e-commerce, even though they have seen promotions through advertisements